A squid‐inspired swimming robot using folding of origami. Issue 10 (10th September 2021) - Hu, Junfeng; Li, Hu; Chen, Weilong
Abstract: Origami enables the folding of objects into a variety of shapes. This paper presents a swimming robot using the folding and unfolding motion of a tabular origami. A squid‐inspired jet propulsion mechanism is used to design an origami swimming robot. The swimming robot utilizes a pulsed‐jet mechanism through the folding motion of the tubular origami structure, which could deform and undulate to provide propulsion for the swimming robot. The robot is incorporated in a stable body, while both swimming forward and steering are generated by the folding motion of the origami structure and undulating fins. An analytical model to investigate the jet propulsion mechanism to capture the relationship between the motor's speed and the generated thrust is developed. The prototype of the swimming robot is fabricated by 3D printing, and experiments verify the robot's components and assembly system. The results show that the swimming robot could achieve swimming forward by folding origami, which could provide unique advantages over other existing underwater propulsion technologies, including scalability and water treatment capabilities. The origami structure provides a novel and simple propulsion mechanism for the swimming robot here, and the mechanism promotes the development of a new class of independent swimming robots.